Characterization of Clostridioides difficile isolates recovered from two Phase 3 surotomycin treatment trials by restriction endonuclease analysis, PCR ribotyping and antimicrobial susceptibilities. (3rd August 2020) - Cheknis, Adam; Devaris, Dominique; Chesnel, Laurent; Dale, Suzanne E; Nary, Julia; Sambol, Susan P; Citron, Diane M; Goering, Richard V; Johnson, Stuart
Abstract: Objectives: To investigate the molecular epidemiology and antimicrobial susceptibility of Clostridioides difficile isolates from patients with C. difficile infection (CDI) from two Phase 3 clinical trials of surotomycin. Methods: In both trials [Protocol MK-4261-005 (NCT01597505) conducted across Europe, North America and Israel; and Protocol MK-4261-006 (NCT01598311) conducted across North America, Asia-Pacific and South America], patients with CDI were randomized (1:1) to receive oral surotomycin (250 mg twice daily) or oral vancomycin (125 mg four times per day) for 10 days. Stool samples were collected at baseline and C. difficile isolates were characterized by restriction endonuclease analysis (REA) and PCR ribotyping. Susceptibility testing was performed by agar dilution, according to CLSI recommendations. Results: In total, 1147 patients were included in the microbiological modified ITT population. Of 992 recovered isolates, 922 (92.9%) were typed. There was a high association between REA groups and their corresponding predominant PCR ribotype (RT) for BI, DH, G and CF strains. REA group A showed more diverse PCR RTs. Overall, the most common strain was BI/RT027 (20.3%) followed by Y/RT014/020 (15.0%) and DH/RT106 (7.2%). The BI/RT027 strain was particularly prevalent in Europe (29.9%) and Canada (23.6%), with lower prevalence in the USA (16.8%) and Australia/New Zealand (3.4%). Resistance was most prevalent in the BI/RT027 strain, particularly to metronidazole, vancomycin and moxifloxacin. Conclusions: A wide variation in C. difficile strains, both within and across different geographical regions, was documented by both REA and ribotyping, which showed overall good correlation.